The Failure of the Heath Government - Holmes, M. author. aut Link
XX, 184 p.
Keywords: Second revised edition of a study of the Conservative government of 1970-74 which discusses and attacks recent revisionist interpretations which exonerate Heath from culpability for the economic and industrial meltdown of 1972-74. Reveals the economic, political and electoral misjudgements of the Heath government.